Pengaruh Agency Costs terhadap Kebijakan Dividen Perusahaan-perusahaan Go Public di Bursa Efek Jakarta - Handoko, Jesica (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2002)
At the real world, the managers and investors are typically not the same people. Oftenly, they don't access the same information these differences frequently cause conflicts between management and investors as owners especially in large firms where managers and owners have different incentive. The cost of problems and conflicts resulting from the separation of the firm or these agency problem is called agency costs. Agency factors that creates agency costs in this research consist of insider ownership , dispersion of ownership , free cash flow and collaterizable assets. Theoritically, dividend policy can be used as one of the mechanisms to reduce the agency problem. This paper investigates the influence of agency costs on dividend policy of companies listed on Bursa Efek Jakarta during the early years of economic crisis (199E - 1999) to see whether that four factors influence dividend policy.